EPR Methods applied on Food Analysis - Drouza, Chryssoula; Spanou, Smaragda; Keramidas, Anastasios D. (My University, 2018)
An overview of the different methodologies developed so far for the investigation of paramagnetic species in foods is presented. Electron paramagnetic resonance spectroscopy (EPR), also known as electron spin resonance spectroscopy (ESR), is the primary technique toward the development of methods for the exploration of EPR-sensitive species, such as free radicals, reactive oxygen species (ROS), nitrogen reactive species (NRS), and C-centered radicals and metal ions. These methods aim for: (a) quantification of radical species, (b) exploration of redox chemical reaction mechanisms in foods, (c) assessment of the antioxidant capacity of food, and (d) food quality, stability, and food shelf life. For these purposes, different radical initiations and detections have been used in foods depending on both the chemistry of the target system and the kind of information required, listed in: the induction of radicals by (a) microwave, UV, or γ-radiation; (b) heating; (c) addition of metals; and (d) use of oxidants.
Keywords: EPR, wines